Dynamic Renal Scintigraphic Estimation of Deceased Donor Kidneys in a Rat Model - Mitil, Huseyin Aydin; Koc, Zehra Pinar; Guzel, Yunus; Kom, Mustafa; Ozer, A. Belin; Ozercan, I. Hanefi; Balci, Tansel Ansal (Medknow Publications & Media Pvt Ltd, 2017)
At present a large number of the renal transplantations are being performed from the deceased donors. The success of these transplantations depends on the viability of the deceased donor kidneys. The aim of this study was to investigate the reliability of scintigraphic estimation of function of deceased donor kidneys by comparing the histopathologic and scintigraphic findings. Ten rats were included in the study (2-3 months old, 250-300 g, all male). Control scintigraphy was performed to all the rats by injection of 37 MBq Tc-99m DTPA from the tail vein in a dynamic manner. Brain death of the rats was achieved by inflation of a Fogartys catheter in the cranial cavity. Immediately, after brain death confirmation, dynamic renal scintigraphy was performed with the same parameters of control scintigraphy. In the comparison of scintigraphies obtained in the before and just after brain death period, there was impairment of tubular functions, concentration and excretion functions in the postbrain death period. In the immediate postbrain death period, there was a significant elevation in the glomerular filtration rate and time to maximum concentration values. In the histopathological evaluation of the kidney samples in the postbrain death period, there were definitive findings of tubular impairment. Dynamic renal scintigraphy also demonstrated definite impairment of tubular system and tubular functions in the deceased donor kidneys. This could explain the reason of the increased frequency of acute tubular necrosis seen among deceased donor kidneys.
Keywords: En-Bloc Kidneys; Cold Ischemia; Graft Function; Transplantation; Allografts; Recipients; Survival